2008
DOI: 10.1371/journal.pone.0003327
|View full text |Cite
|
Sign up to set email alerts
|

Reference Ranges for the Clinical Laboratory Derived from a Rural Population in Kericho, Kenya

Abstract: The conduct of Phase I/II HIV vaccine trials internationally necessitates the development of region-specific clinical reference ranges for trial enrolment and participant monitoring. A population based cohort of adults in Kericho, Kenya, a potential vaccine trial site, allowed development of clinical laboratory reference ranges. Lymphocyte immunophenotyping was performed on 1293 HIV seronegative study participants. Hematology and clinical chemistry were performed on up to 1541 cohort enrollees. The ratio of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

80
149
24

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 113 publications
(270 citation statements)
references
References 35 publications
80
149
24
Order By: Relevance
“…Similar findings were noted in Rwanda [8]. Sex differences in UA have been previously documented by Roche Diagnostics, Eller et al, Saathoff et al and Khan et al [2,4,5,9] which could be due to the influence of sex hormones resulting in differences in body mass between sexes. The general absence of sex differences for BUN, CA, and PHOS in this study agrees with those reported in the reagent manufacturer's reference range values [2]; the result is similar to studies done in Pakistan [10], an indication that these parameters are not influenced by sex hormones.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Similar findings were noted in Rwanda [8]. Sex differences in UA have been previously documented by Roche Diagnostics, Eller et al, Saathoff et al and Khan et al [2,4,5,9] which could be due to the influence of sex hormones resulting in differences in body mass between sexes. The general absence of sex differences for BUN, CA, and PHOS in this study agrees with those reported in the reagent manufacturer's reference range values [2]; the result is similar to studies done in Pakistan [10], an indication that these parameters are not influenced by sex hormones.…”
Section: Discussionsupporting
confidence: 85%
“…Male creatinine values for the current study were lower than those for America, Kericho and Kuwait groups [2,5,11], greater than those for Tanzanian population [3] and comparable with those of the Uganda group [4]. North Rift female creatinine values were higher than the America, Mbeya, and Kampala [2][3][4] but lower than those for Kericho populations [5].…”
Section: Discussionmentioning
confidence: 41%
See 3 more Smart Citations